Efektifitas Model Pembelajaran Inkuiri dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Kewarganegaraan - Mustaricha, Mitra; Rochmadi, Nur Wahyu (Universitas Negeri Malang, 2019)
This study aims to examine the effectiveness of inquiry learning models in improving students’ critical thinking skills on Pancasila and Citizenship Education subjects. This type of research uses quasi experimental design. The experimental design that is used as a reference is “pretest-posttest non equivalent group design”. The results showed that the inquiry learning model can improve students’ critical thinking skills. Hypothesis testing using the t-test analysis technique shows that the inquiry learning model is effective in increasing students’ critical thinking skills in PPKn subjects with a significance value of 0.0001.